2013
DOI: 10.1002/jlcr.3171
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging and pharmacokinetics of 99mTc‐hTERT antisense oligonucleotide as a potential tumor imaging probe

Abstract: Targeting and visualization of human telomerase reverse transcriptase (hTERT) represents a promising approach for providing diagnostic value. The uptake kinetics and imaging results of (99m) Tc-hTERT antisense oligonucleotides (ASON) in hTERT-expressing cells were examined in vitro and in vivo. The pharmacokinetics and acute toxicity studies of (99m) Tc-hTERT ASON were also performed. The labeling efficiencies of radiolabeled oligonucleotide reached 76 ± 5%, the specific activity was up to 1850 kBq/µg, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…In addition, there was no significant difference in radioactivity accumulation between naked ASON and carrier-mediated ASON. These results demonstrated that Lipofectamine and Xfect TM transfection reagent could deliver the ASON into cells in vitro efficiently but not be effective in vivo, which was in accordance with a recent research [16].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, there was no significant difference in radioactivity accumulation between naked ASON and carrier-mediated ASON. These results demonstrated that Lipofectamine and Xfect TM transfection reagent could deliver the ASON into cells in vitro efficiently but not be effective in vivo, which was in accordance with a recent research [16].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the cell accumulation of radiolabeled ASON probes increased significantly (pG0.05) after binding with transfection reagents. The increase in cellular uptake following binding with the carriers was in accordance with the previous studies [16,22]. Furthermore, The CLSM imaging showed that the fluorescence intensity in transfection groups (Lipo-ASON and Xfect-ASON) was clearly higher than that in controls…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While telomerase per se could be targeted for imaging, this activity has not been reported in the field of PET. Liu et al have reported a SPECT probe for detecting human telomerase reverse transcriptase (hTERT), the major component of telomerase activity, using antisense oligonucleotides ( 99m TchTERT ASON) [114]. Though higher tracer accumulation was observed in vivo in MCF7 xenografts compared to labelled control sense oligonucleotides, image quality was compromised due to high background.…”
Section: Imaging Proliferation Growth and Replicative Immortalitymentioning
confidence: 98%